Factor Graph Based Joint Detection/Decoding for LDPC Coded Large-MIMO Systems - Narasimhan, T. L.; Chockalingam, A.; Rajan, B. S. (2012 IEEE 75th Vehicular Technology Conference (VTC Spring), 2012)
In this paper, we employ message passing algorithms over graphical models to jointly detect and decode symbols transmitted over large multiple-input multiple-output (MIMO) channels with low density parity check (LDPC) coded bits. We adopt a factor graph based technique to integrate the detection and decoding operations. A Gaussian approximation of spatial interference is used for detection. This serves as a low complexity joint detection/decoding approach for large dimensional MIMO systems coded with LDPC codes of large block lengths. This joint processing achieves significantly better performance than the individual detection and decoding scheme.